Characteristic Skin Eruptions with a Distinct Histological Pattern Allow Early Diagnosis of Vitamin C Deficiency - Goran Mirkovic; Markus Reinhold Mutke; Beda Muehleisen (Case Reports in Dermatology, 2024)
Introduction: Scurvy has become a rare disease in western countries with potentially high morbidity. Early diagnosis is crucial and can be challenging. Case Presentation: We present the case of a 56-year-old male patient who developed hemorrhagic diathesis after trivial impact trauma. Previously, the patient suffered from fatigue and loss of appetite. Characteristic skin eruptions and a distinct skin histology along with a decreased serum vitamin C level led to the diagnosis of scurvy. Following vitamin C supplementation, symptoms improved rapidly. Conclusion: In conclusion, vitamin C deficiency should be considered in cases with unclear hemorrhagic diathesis and a medical history of nutritional irregularities. Especially in cases of scurvy that do not yet show the full clinical spectrum of symptoms or have only moderately decreased serum vitamin C levels, thorough clinical dermatological examination and a skin biopsy are essential for early diagnosis and to prevent complications.